People against the challenges of the era: The English Department at the Jagiellonian University (1945–1952) – an outline of the problem - Tomasz Pudłocki (Studia Historiae Scientiarum)
This article provides a brief history of the English Department at the Jagiellonian University from 1945 to 1952. It presents the members of the staff and discusses their background and responsibilities as well as problems they faced in the new post-war reality. After the death of Prof. Roman Dyboski, the founder and first Head of the Department, and the arrest of his successor, Prof. Władysław Tarnawski, formerly affiliated with the University of Lvov, the staff were mainly of junior academic ranks, with no involvement in any serious research. Despite that and despite a perennial shortage of space and problems with logistics, the number of students enrolling in the English studies programme would increase each year making the Department grow in size and scope. Thanks to the help of the New York Kosciuszko Foundation, the Department received a collection of several thousands of books, a few young American grantees of the Foundation joined the teaching staff, and some of the outstanding academics and students (e.g. Przemysław Mroczkowski and Alfred Reszkiewicz) obtained funding support to study or conduct research abroad. For ideological reasons, however, Poland’s authorities closed the programme, which ultimately led to the closure of the Department in 1952.